Removal of Interictal MEG-Derived Network Hubs Is Associated With Postoperative Seizure Freedom - Ramaraju, Sriharsha; Wang, Yujiang; Sinha, Nishant; McEvoy, Andrew W.; Miserocchi, Anna; de Tisi, Jane; Duncan, John S.; Rugg-Gunn, Fergus; Taylor, Peter N. (Frontiers in Neurology, 2020)
Objective: To investigate whether MEG network connectivity was associated with epilepsy duration, to identify functional brain network hubs in patients with refractory focal epilepsy, and assess if their surgical removal was associated with post-operative seizure freedom. Methods: We studied 31 patients with drug refractory focal epilepsy who underwent resting state magnetoencephalographic (MEG), and structural magnetic resonance imaging (MRI) as part of pre-surgical evaluation. Using the structural MRI, we generated 114 cortical regions of interest, performed surface reconstruction and MEG source localisation. Representative source localised signals for each region were correlated with each other to generate a functional brain network. Network hubs were defined as those with the highest intra-hemispheric mean correlations. Post-operative MRI identified regions that were surgically removed. Results: Greater mean MEG network connectivity was associated with a longer duration of epilepsy. Patients who were seizure free after surgery had more hubs surgically removed than patients who were not seizure free (AUC=0.76, p=0.01) consistently across three randomly chosen time segments. Conclusion: Our results support a growing literature implicating network hub involvement in focal epilepsy, the removal of which by surgery is associated with greater chance of post-operative seizure freedom.